A randomised pilot trial of the anti-von Willebrand factor aptamer ARC1779 in patients with type 2b von Willebrand disease - Jilma, Bernd; Paulinska, Petra; Jilma-Stohlawetz, Petra; Gilbert, James C.; Hutabarat, Renta; Knöbl, Paul (Thrombosis and Haemostasis, 2010)
Desmopressin aggravates thrombocytopenia in type 2B von Willebrand disease (VWF type 2B) by release of large and hyper-adhesive von Wille-brand Factor (VWF) multimers. This pilot study investigated whether the anti-VWF aptamer ARC1779 can prevent desmopressin-induced thrombocytopenia and interferes with the excessive VWF turnover in patients with VWF type 2B. Concentration effect curves of ARC1779 were established for five patients in vitro and two patients with VWF type 2B were treated by infusion of ARC1779, desmopressin, or their combination in a randomised, controlled, double-blind design. ARC1779 concentrations in the range of 1–3 μg/ml blocked free A1 domain binding sites by 90% in vitro. In vivo, desmopressin alone induced a profound (-90%) drop in platelet counts in one of the patients. ARC1779 (4–5 μg/ml) completely inhibited VWF A1 domains and prevented this desmopress-in-induced platelet drop. Desmopressin alone increased VWF antigen two- to three-fold, accompanied by concordant changes in VWF Ristocetin cofactor activity (RCo) and coagulation factor VIII activity. ARC1779 substantially enhanced the desmopressin-induced maximal increase in these parameters, and improved multimer patterns. No treatment related adverse events were observed and no bleeding occurred despite marked thrombocytopenia. These data provide first proof of concept in humans and evidence that ARC1779 is a potent inhibitor of VWF. ARC1779 prevented the rapid consumption of VWF multimers together with agglutinated platelets that occurred in response to desmopressin challenge in patients with VWD type 2B.Clinical Trial registration number: NCT00632242.
Keywords: Clinical trials; antiplatelet drugs; von Willebrand factor; thrombocytopenia; desmopressin